The Application Of Justice Principles Of Rapid Simple Fee In Criminal Justice System In The State Court (Case Study in State court of Pati) - Lailatul Nur Hasanah; Sri Endah Wahyuningsih (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aims to determine and analyze the application of the principle of simple justice Rapid Simple Fee in the criminal justice system in the State court of Pati. As well as to identify and explain the barriers and solutions simple application of the principle of justice Rapid Simple Fee in the judicial system in State court of Pati. And to identify and explain the contribution principle is simple justice Rapid Simple Fee in the criminal justice system to reform the criminal justice system in the future. This study uses empirical juridical approach to analysis of the application of the principle of judicial issues simple, quick and inexpensive in the criminal justice system in the State court of Pati. Specifications research is descriptive analysis. With data collection techniques are primary and secondary data and research literature, analyzed using qualitative. The problem is analyzed with the theory of law enforcement and progressive legal theory. The results of this study showed that every judge shall comply with the laws that have been set ie power Act No. 48 of 2009 and Act No. 8 of 1981. Constraints in principle to simple justice Rapid Simple Fee is the human resources of the apparatus law enforcement, lack law enforcement and courtroom facilities, absence of the parties or witnesses. The solution is to determine the court calendar, giving sanction to the litigants or witnesses who have been called State court of Pati. Contributions in future expected law enforcement qualified for handling the case, mutual cooperation between law enforcement agencies and is able to imitate the criminal justice system in developed countries such as settling disputes out of court with mediation mechanism penal (penal mediation), restorative justice, diversion in juvenile justice and other forms that thrive in the community. It is considered necessary as part of the criminal law reform. Contributions in future expected law enforcement qualified for handling the case, mutual cooperation between law enforcement agencies and is able to imitate the criminal justice system in developed countries such as settling disputes out of court with mediation mechanism penal (penal mediation), restorative justice, diversion in juvenile justice and other forms that thrive in the community. It is considered necessary as part of the criminal law reform. Contributions in future expected law enforcement qualified for handling the case, mutual cooperation between law enforcement agencies and is able to imitate the criminal justice system in developed countries such as settling disputes out of court with mediation mechanism penal (penal mediation), restorative justice, diversion in juvenile justice and other forms that thrive in the community. It is considered necessary as part of the criminal law reform.Keywords: Principle of Simple Justice, Rapid Simple Fee In Criminal Justice System in Pati Court